In front of the retreating ice-sheet: Fauna complex of Central Poland in MIS 3–2 (Krosinko site) - Pawłowska, Kamilla (Elsevier, 2023)
A new locality in Central Europe (Krosinko, Poland) yields a rich fossil material of great taxonomical variety. Its location in the Warsaw–Berlin ice-marginal valley, where it forms a 1-m horizon at a the depth of 6–8 m, is suited to a taphonomic analysis aimed at reconstructing the paleoevents and depositional history of the late Pleistocene (MIS 3–2). Our analysis revealed that the material accumulated as the result of high-energy fluvial transport. This transport disturbed the original bone associations, as indicated by the lack of articulation, low refitting, and bone surface modification. During water movement, the bones were polished, abraded, pitted, and fragmented. Prior to that, however, taphonomic signatures were left behind by predators, humans, and plant roots. This is the first time that unquestionable burning marks have been found on woolly rhino remains from Poland. The secondary context of the faunal assemblage was confirmed by neodymium isotope studies of the faunal fragments and sediment. Given the results of sedimentological analysis from previous studies, these sediments can be associated with a high-energy braided river. The remains were moved along with paleobotanical material and flints in a westerly direction; this is suggested by the direction of water flows in the valley and the river waters supplying it. The deposition occurred within a single geologic event around 26 ka BP, as indicated by the youngest radiocarbon date of the remains, or ca. 19 ka BP, considering the geochronological constraints for the local LGM ice margin position in central and eastern Poland ~22–18 ka, and the specified accumulation time of the sediments in which they were found. Secondary mineralization of manganese and iron on the bones was the final taphonomical process that impacted the remains. The combined taphonomic, palaeozoological, isotopic and geological results show for the first time for a Polish paleontological site how data integration improves interpretation and highlights the advantages of a multiproxy approach.
Keywords: Mammals; Taphonomy; Isotopes; Late Pleistocene; MIS 3–2; Poland